THE INFLUENCE OF SCHOOL WELL BEING ON STUDENT ENGAGEMENT: DOES SELF-REGULATED LEARNING MEDIATE? - Siti Rahma; Rahmi Lubis; Amanah Surbakti (Program Studi PGSD Universitas Flores, 2025)
Student engagement in learning is important to improve so that students can achieve success in their studies. The purpose of the study was to examine the effect of school well being on student engagement, the effect of school well being on self-regulated learning, the effect of self-regulated learning on student engagement, and the effect of school well being on student engagement on self-regulated learning as a mediating variable. This research uses quantitative methods, data was collected from 219 samples. In this study, the sampling technique used was cluster random sampling. The results of this study indicate that there is an effect of school well being on student engagement, with a coefficient value of 0.161, t-statistic=2.868, and p-value=0.004. There is an effect of school well being on self-regulated learning with a coefficient of 0.183, t-statistic=2.198, and p-value = 0.028. There is an effect of self-regulated learning on student engagement with a coefficient of 0.423, t-statistic=7.295, and p-value=0.000. There is an effect of school well being on student engagement with self-regulated learning as mediation, with a mediation coefficient of 0.077 with a t-statistic of 1.961 and a p-value of 0.050 indicating that this mediation effect is significant at the 5% significance limit.